2013
DOI: 10.1017/s0025315413001574
|View full text |Cite
|
Sign up to set email alerts
|

Leaf-litter decomposition of the mangrove speciesAvicennia schaueriana,Laguncularia racemosaandRhizophora mangle

Abstract: This study evaluated the decomposition process of leaf litter from the main Brazilian mangrove species Avicennia schaueriana, Laguncularia racemosa and Rhizophora mangle. Senescent leaves were collected, dried and placed in nylon bags with different mesh sizes (fine: 2 × 2 mm and coarse: 8 × 8 mm). The bags were distributed over the sediment, and replicates of each species and mesh size were collected periodically over 4 months. In the laboratory, the dry weight of the samples was measured, and the decompositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
1
6
0
3
Order By: Relevance
“…This process would explain why mangrove-derived nutrients in our study were assimilated by consumers inside the mangrove wetland, but not by consumers in the adjacent marine area, despite observations of mangrove leaves in adjacent sandy beaches. The mangrove-derived material found in the sandy beaches most likely could not be assimilated by local consumers due its more refractory characteristic (Rodelli et al 1984) and lower nutritional value (Lima et al 2014), similar to what has been observed in other coastal systems (Rodelli et al 1984, Hemminga et al 1994). …”
Section: Trophic Connectivity Between Estuarine and Ocean Habitatssupporting
confidence: 65%
See 2 more Smart Citations
“…This process would explain why mangrove-derived nutrients in our study were assimilated by consumers inside the mangrove wetland, but not by consumers in the adjacent marine area, despite observations of mangrove leaves in adjacent sandy beaches. The mangrove-derived material found in the sandy beaches most likely could not be assimilated by local consumers due its more refractory characteristic (Rodelli et al 1984) and lower nutritional value (Lima et al 2014), similar to what has been observed in other coastal systems (Rodelli et al 1984, Hemminga et al 1994). …”
Section: Trophic Connectivity Between Estuarine and Ocean Habitatssupporting
confidence: 65%
“…According to our mixing isotope models, L. racemosa was the only mangrove tree out of the three species occurring in this estuary that contributed significant amounts of nutrients to consumers. This species is comparatively dominant in the inner region of the estuary (Iaponira, 2009) and is characterized by a higher nutritional value than R. mangle (Lima et al 2014), which is dominant nearer the southern portion of the estuary. A proxy for the nutritional value is the C:N ratio because lower values indicate higher amounts of nitrogen than carbon and, consequently, a higher nutritional value to consumers (Ashton et al 1999).…”
Section: Food Assimilation Across the Environmental Gradientmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Las comparaciones de medias arrojaron diferencias estadísticamente significativas (Wilcoxon, p < 0.05) en la mayoría de variables físico-bióticas CUADRO 1 Valores promedio de las variables ambientales para tres manglares en la Bahía de Cispatá, Colombia (media ± desviación estándar) (Kristensen, Holmer, Banta, Jensen, & Hansen, 1995;Kathiresan & Bingham, 2001, Lima & Colpo, 2014. Adicionalmente, en bosques inundados, como los de borde de este trabajo, la descomposición de hojarasca es retardada por la reducción de oxígeno y el C queda almacenado en el suelo (Valdés-Velarde, 2010).…”
Section: Estructura De Los Manglaresunclassified
“…Esto justifica que los mayores valores de C total en el sedimento de los manglares de la bahía de Cispatá se encuentren en los de tipo cuenca. La tasa de descomposición de hojas de L. racemosa es más lenta que la de hojas de R. mangle, pero más rápida que la de A. germinans (Lima & Colpo, 2014). En el manglar de borde B, L. racemosa explica el mayor contenido de C respecto al de borde A. Valdés-Velarde (2010) registró mayor contribución al contenido de C en suelos cuando predominan tanto A. germinans como L. racemosa.…”
Section: Estructura De Los Manglaresunclassified